Bringing optimised COVID-19 vaccine schedules to immunocompromised populations: statistical elements and design - Michael Dymock; James H. McMahon; David Griffin; Michelle Hagenauer; Tom L. Snelling; Julie A. Marsh; On behalf of the BOOST-IC Investigator Team (Trials)
Abstract Bringing optimised coronavirus disease 2019 (COVID-19) vaccine schedules to immunocompromised populations (BOOST-IC) is a multi-site, adaptive platform trial designed to assess the effect of different booster vaccination schedules in the Australian immunocompromised population on the immunogenicity, safety and cross-protection against COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its variants. Participants from one of three immunocompromised subpopulations (people living with human immunodeficiency virus, solid organ transplants or haematological malignancies) are randomised to receive a one- or two-dose booster vaccination schedule using one of three COVID-19 vaccine brands (Pfizer, Moderna or Novavax) available in Australia. The primary endpoint is the SARS-CoV-2 anti-spike immunoglobulin G concentration at 28 days after the final dose of study vaccine and is modelled using a Bayesian hierarchical two-part model, anticipating that a significant proportion of responses may be below the limit of assay detection. We describe the structure and objectives of the BOOST-IC trial and how these are mathematically represented, modelled and reported, including specification of the estimands, statistical models and decision criteria for trial adaptations. This paper should be read in conjunction with the BOOST-IC study protocol. BOOST-IC was registered on 27 September 2022 with the Australian and New Zealand Clinical Trials Registry NCT05556720.